Differential scanning calorimetric investigations of three rotary nickel-titanium instrument systems before and after simulated clinical uses - Khoa Van Pham (BMC, 2021)
Abstract Background The transformation temperatures were important values, influencing the mechanical properties and clinical performance of nickel-titanium instruments. The aim of this study was to determine the transformation temperatures of three rotary nickel-titanium (NiTi) instruments: Reciproc, HyFlex CM Pro, and Neoniti before and after simulated clinical uses. Methods Ninety new NiTi instruments of three single-file instruments: Reciproc, HyFlex CM Pro, and Neoniti were divided into three groups. Thirty instruments of each group were divided into 3 subgroups (10 instruments for each subgroup): new, one-time simulated clinical used and sterilised, and three times simulated clinical used and sterilized subgroups. The instruments were in the as-received condition for the new subgroups, one time used in the plastic endo-training blocks and sterilised for the one-time subgroups, and three times used in the plastic endo-training blocks and sterilised for the three times subgroups. Each instrument in subgroups was cut into four small segments of 4-5 mm. All segments of instruments were analysed using Differential Scanning Calorimetry (DSC). Data was collected and analysed using SPSS version 20.0 with ANOVA test or Kruskal-Wallis test at the significant level of 0.05. Results There was not significant difference between before and after simulated clinical use with sterilised procedure in three NiTi instrument systems. The austenite-finish (Af) temperatures of three instrument systems were higher than that of the human body (37 °C), of these, the Af temperature of Neoniti was highest and that of HyFlex CM Pro was lowest. Conclusions The austenite-finish (Af) temperatures of three NiTi instruments were higher than that of human body temperature, therefore, material was in the phase transformation from martensite to austenite, gives the instruments more flexibility when used in the clinical situation.